Characterization of the Active Ingredient and Prediction of the Potential Mechanism of Dahuoluo Pill via Mass Spectrometry with the Network Pharmacology Method - Haoran Xu; Yuelin Bi; Xin Feng; Jiaqi Wang; Gengyuan Yu; Tonghua Zhang; Tianyi Li; Xuhua Gao; Runhua Liu; Yu Sun; Hao Wu; Linlin Fang; et al. (Journal of Analytical Methods in Chemistry)
The Dahuoluo pill (DHLP) is a classic Chinese patent medicine used to treat rheumatoid arthritis and other conditions. However, there has been no research on the chemical components of DHLP and the mechanisms by which it ameliorates rheumatoid arthritis. Hence, we analysed the chemical components of DHLP and the DHLP components absorbed in blood by using ultraperformance liquid chromatography-Q-exactive-orbitrap-mass spectrometry. We then used network pharmacology to predict the underlying mechanisms by which DHLP ameliorates rheumatoid arthritis. We identified 153 chemical compounds from DHLP, together with 27 prototype components absorbed in blood. We selected 48 of these compounds as potential active ingredients to explore the mechanism. These compounds are related to 88 significant pathways, which are linked to 18 core targets. This study preliminarily reveals the potential mechanisms by which DHLP ameliorates rheumatoid arthritis and provides a basis for further evaluation of the drug’s efficacy.